CLIL Implementation in Selected STEM Departments at the University of Sulaimani - Abdulkareem, Raman Qalandar Hussein (Sulaimani Journal for Humanities, 2025)
English language has influenced and occupied the world in many aspects such as economic, social, political and educational system. Kurdistan Region is no exception in this regard. Learning English, as a foreign language (EFL), has been the demand of the majority, which led to the emergence of EMI (English as a Medium of Instruction). All these termed for an innovative form of education, content and language integrated learning (CLIL) has been the response. CLIL is an educational method by which subjects are taught through a foreign language with dual-focused aims, namely learning the content, and learning a foreign language simultaneously. This paper is about the implementation of CLIL in the selected science, technology, engineering, and math (STEM) departments at the University of Sulaimani. It presents how some selected teachers, on individual basis, have implemented CLIL method in the STEM departments voluntarily. The study hypothesizes that it is more effective to learn English language in integration with the content. As a result, this study finds out that learning a language through content is one of the best methods to have control of both knowledge and language together at the same time.
Keywords: CLIL; EMI; implementation; STEM; cooperation